A distributed extended reality escape method for layered underground infrastructure based on AI game engine - Li, Wei; Wang, Linbing; Sun, Maogui; Yin, Dengcai; Wang, Yajian; Zhou, Xiang; Wang, Yongming; Ye, Zhoujing (Journal of industrial information integration, 2026)
As the structural carrier of mineral resources, underground mine is a typical artificial large layered underground infrastructure. The safety of mining systems remains a critical concern for nations worldwide. Based on the environmental characteristics of underground mines, the accompanying safety issues are evident. Conventional personnel evacuation drills for mine disasters often fail to create effective disaster evolution memories for people. When a real accident occurs, people cannot escape efficiently in a panic state, which reduces survival probability. To solve this problem, an escape space connection algorithm is developed based on the physical information and management rules in this study, and it is used to drive the extended reality escape system by the game engine. Firstly, this study takes the water-inrush accidents of underground layered mines as the engineering research object and background, the characteristics of water-inrush accidents evolution and personnel evacuation are systematically analyzed based on the scenario construction theory. Secondly, this study develops an escape space connection algorithm by integrating the two-dimensional A* algorithm and the connection weights of escape spaces based on the spatial geometric information and escape strategy of layered mines. Thirdly, a distributed extended reality (XR) human-computer interaction system is developed for escape path guidance in real environments based on the spatial structure characteristics of layered mines and the escape space connection algorithm. Finally, application testing is conducted in the experimental mine to analyze the system performance and future application potential. This study provides a comprehensive technical framework for personnel evacuation in layered underground infrastructure during evolutionary accidents, and the theories and systems involved are universal. In addition, this method can be used as a new, low-cost and efficient digital reference system for personnel safety emergency drills in underground infrastructure.